2021
DOI: 10.1007/s10067-021-05981-4
|View full text |Cite
|
Sign up to set email alerts
|

Stachys schtschegleevii tea, matrix metalloproteinase, and disease severity in female rheumatoid arthritis patients: a randomized controlled clinical trial

Abstract: Background Stachys schtschegleevii (SSC) is a herbal medicine used to treat infections. To date, this is the first study aimed to investigate the effects of SSC tea on disease activity score (DAS), serum inflammatory biomarkers and matrix metalloproteinases (MMP-1 and MMP-3) among women with rheumatoid arthritis (RA). Methods This pilot, triple-blind, randomized controlled clinical trial was conducted among forty-four women (age: 30-65 years) diagnosed with moderately active RA. Subjects were randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Mirtaheri et al., 2021 showed that no adverse effects of treatment were recorded in the tea polyphenol group and the control group ( 57 ). Alghadir et al., 2016 did not report any adverse reactions, possibly because they were not monitored ( 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mirtaheri et al., 2021 showed that no adverse effects of treatment were recorded in the tea polyphenol group and the control group ( 57 ). Alghadir et al., 2016 did not report any adverse reactions, possibly because they were not monitored ( 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding herbal studies, Nigella sativa extract (500 mg twice daily for 2 months) significantly decreased CRP levels and DAS28 scores [ 114 ]. Stachys schtschegleevii tea (2.4 g daily for 8 weeks) markedly reduced DAS-28 scores and serum MMP-3 levels [ 115 ]. Xinfeng supplement (three pills, three times a day for 2 months) significantly decreased the DAS-28 score, ESR, and CRP levels [ 116 ].…”
Section: Natural Foods Phytochemicals and Chemical Compounds With Ant...mentioning
confidence: 99%
“…[46] In studies conducted with different species of the Stachys genus in the literature, it has been observed that the genus effectively regulate cell proliferation due to its abundant secondary metabolites. [47][48][49][50] For instance, when Stachys parviflora was applied to the uncontrolled proliferation of breast cancer cell lines MCF-7 and MDA-MB-231, as well as the prostate cancer cell line PC3, it effectively inhibited cell proliferation and induced apoptosis. [49] In another study, Stachys pilifera treatment was found to regulate cell death mechanisms and proliferation in the colon cancer cell line HT-29.…”
Section: Determination Of Cytotoxicity and Cell Proliferation Effect ...mentioning
confidence: 99%